Analysis of the efficiency of theoretical knowledge and practical skills acquisition by intern doctors using the "Body Interact" virtual patient simulator in the conditions of today's challenges - M. Yu. Kolesnyk; Ya. M. Mykhailovskyi (Zaporozhye State Medical University, 2024)
The aim of the work is to evaluate the efficiency of theoretical knowledge and practical skills acquisition by intern doctors using the body interact virtual patient simulator in distance (offline) and traditional (online) form of education. Materials and methods. The study involved 22 interns in the second year of study of the specialty "Internal Diseases". 17 of them studied in offline format, 5 - in distance (online) format. The efficiency of theoretical knowledge acquisition was evaluated based on the results of the Integrated License exam "KROK 3. General Medical Training". The efficiency of practical skills acquisition was determined by passing scenarios of providing medical care using the virtual patient simulator "Body Interact". Results. It has been established that the effectiveness of traditional (offline) and distance (online) learning is comparable in terms of theoretical knowledge acquisition which is evidenced by the comparative results of passing the Integrated License exam "KROK 3. General Medical Training". The results of passing the state license integrated exam "KROK 3. General medical training" and the virtual patient "Body Interact" had no correlation, which indicates the insufficient representativeness of the test assessment regarding the practical skills acquisition. Traditional (offline) learning is more effective in practical skills acquisition, which is confirmed by the better results of passing scenarios of providing medical care using the virtual patient program "Body Interact" in the group of traditional form of education compared to the group of online learning. Conclusions. Utilizing virtual patient simulation technology such as "Body Interact" in the training of intern doctors not only enhances the acquisition of theoretical educational material but also offers an opportunity to practice practical skills. This is particularly valuable in light of resource constraints resulting from COVID-19 and martial law. Implementing the "Body Interact" virtual patient technology into daily educational practices, especially in the context of distance learning, is advisable.